Heuristics evaluation of preschool cognitive skills learning system - Abbas, M.A. (2013)
The ubiquitous use of computer by children is highly perceptible in current research. Therefore, providing the increasing interaction to computer technologies demands a careful designing of these technologies keeping in view the pedagogical aspects, psychology, abilities and interests of the children. These requirements make development of such applications a very complex job. Therefore, existing applications follow the content delivery model i.e. previously crafted contents are stored to deliver to a user. This limits the effective learning of the children. The present work proposed a rule-based system utilizing semantic web technologies (Ontologies) as a domain knowledge and semantic web rule language (SWRL) for rules representation. The proposed system overcomes the complexity of developing the intelligent and interactive applications for children. Evaluation is performed by using formal usability evaluation heuristics over an application developed using our proposed system for preschool cognitive skills tutoring. Results provided here demonstrates that the underlying knowledge modeled through the use of Ontologies is highly supported to flexible and child-friendly interfaces and pedagogical and playability activities (motor, reasoning) for cognitive skills tutoring. Â© 2013 Springer International Publishing.